2017
DOI: 10.1037/bne0000222
|View full text |Cite
|
Sign up to set email alerts
|

Across sex and age: Learning and memory and patterns of avian hippocampal gene expression.

Abstract: Age-related decrements in cognitive ability have been proposed to stem from deteriorating function of the hippocampus. Many birds are long lived, especially for their relatively small body mass and elevated metabolism, making them a unique model of resilience to aging. Nevertheless, little is known about avian age-related changes in cognition and hippocampal physiology. We studied spatial cognition and hippocampal expression of the age-related gene, Apolipoprotein D (ApoD), and the immediate early gene Egr-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…Previous work has mainly focused on the role of the hippocampus in spatial memory performance ( Macphail, 2002 ). Prior studies demonstrated that males generally outperform females in spatial memory performance tasks, but rely on different strategies in learning such cognitive tasks in both mammals and songbirds ( Kosarussavadi et al, 2017 ; Rensel et al, 2015 ; Tropp and Markus, 2001 ). Sexually different learning mechanisms have also been suggested in vocal learning in songbirds ( Riebel, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has mainly focused on the role of the hippocampus in spatial memory performance ( Macphail, 2002 ). Prior studies demonstrated that males generally outperform females in spatial memory performance tasks, but rely on different strategies in learning such cognitive tasks in both mammals and songbirds ( Kosarussavadi et al, 2017 ; Rensel et al, 2015 ; Tropp and Markus, 2001 ). Sexually different learning mechanisms have also been suggested in vocal learning in songbirds ( Riebel, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reference Collection 17 (Simard et al, 1990(Simard et al, , 1991(Simard et al, , 1992Sugimoto et al, 1994;Patel et al, 1995;Harding et al, 2000;Zhou et al, 2000;Yao and Vieira, 2002;Appari et al, 2009;Do Carmo et al, 2009a;Wang et al, 2010;Chen et al, 2011;Tapia et al, 2011;Delattre et al, 2012;Eigeliene et al, 2012;Pérez et al, 2012;Germeyer et al, 2013;Jeong et al, 2015;Tao et al, 2017;Kfir et al, 2018;Hornig et al, 2019;Igarashi et al, 2020). Reference Collection 18 (Loerch et al, 2008;de Magalhães et al, 2009;Kim et al, 2009;Bianchi-Frias et al, 2010;Navarro et al, 2010bNavarro et al, , 2013Martínez et al, 2012Martínez et al, , 2013Ordóñez et al, 2012;Yan et al, 2012;Sanchez et al, 2015;Martineau et al, 2016;Kosarussavadi et al, 2017;García-Mateo et al, 2018;Waldner et al, 2018;Yu et al, 2020).…”
Section: Apod Systematic Review Reference Collectionsunclassified
“…Females showed also a higher egr-1 expression than their male counterparts. The same was observed with respect to ApoD expression levels in young zebra finches, possibly indicating neurobiological compensation of older birds (Kosarussavadi et al, 2017). At the same time, there is the advantage of being able to respond rapidly and dynamically to new contexts and adjust decisions via novel, flexible connections between the brain regions involved ('functional reconfiguration of connectivity' , Sporns, 2010).…”
Section: Sex Differences: Cognitive Processesmentioning
confidence: 52%
“…Additionally, age-and environment-dependent sex-specific differences in hippocampal morphology, cell signaling, synaptic plasticity, and activity in performing memory tasks have been reported in numerous mammalian species including humans and rodents (compare Koss and Frick, 2016 for review). Likewise, sex-specific differences were found in the age-dependent altered neuronal gene activity in the hippocampus of different-aged zebra finches (Kosarussavadi et al, 2017). In analogy to the domain-specific cognitive involvement of different brain nuclei, different patterns of gene activity are also reflected in the respective recruitment of multiple neuronal circuits depending on a social context Hofmann, 2011, 2012).…”
Section: Sex Differences: Cognitive Processesmentioning
confidence: 97%